Reduction of fibre bundle G(G/H, H) over submanifolds of space G/H. II - Vosylius, R. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Восилюс. Редукция расслоения G(G/H,H) над подмногообразиями пространства G/H. II R. Vosylius. Išsluoksniavimo G(G/H, H) redukcijos virš erdvės G/H podaugdarių, II